Outcome of conjunctival autograft transplantation in pterygium surgery in a community based hospital in Nepal - Sharma, R; Marasini, S; Nepal, B P (Nepalese Journal of Ophthalmology, 2012)
Introduction: The mainstay of treatment for pterygium is surgical excision with or without a graft. The most common problem with this intervention is recurrence, for which a multitude of factors have been described. Objective: To evaluate the recurrence rate of pterygium in conjunctival autologous graft transplantation after its excision in people living in a hilly region of Nepal Materials and methods: A prospective interventional study was conducted in patients undergoing pterygium excision with conjunctival autologous graft transplantation. The patients were followed up for 20 months. Any recurrence of pterygium was noted during this period. Results: Thirty four patients with an age range of 29 to 65 years (mean 43.88±9.19 years) were included. Female predominated (n=21, 61.8%) in the study. Service holders formed a majority of the cases (n=14, 41.2%) followed by farmers (n=10, 29.4%, OR 0.019, 95% CI = 0.002 to 0.209). Ocular discomfort was the main presenting complaint. Dry eye was seen in 30 patients (88.23%). Most of the patients (26, 76.5%) had a grade II pterygium. Graft displacement was the main complication in two (5.88%) patients and recurrence of pterygium was found in three (8.82%). Conclusion: Conjunctival autologous transplantation is a safe and effective method for the treatment of pterygium with a minimal recurrence rate. DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6539 Nepal J Ophthalmol 2012; 4 (2): 242-247